An Analysis of the Reliability of Protection System in Rectorate building of Muhammadiyah Riau University: Analysis of the Reliability of Protection System in Rectorate building of Muhammadiyah Riau University - Setiawan, Bima Yulio; Iriana, Rian Trikomara; Djuniati, Sri (Departemen Teknik Sipil, Fakultas Teknik Universitas Riau, 2023)
Fire is a frequent occurrence especially for tall buildings, so it is veryn ecessary to have a reliable fire protection system for a building. Including the Rectorate building of Muhammadiyah Riau University which is a combined building between the rectorate secretariat building, University hall, University library and a place to take care of all administrative matters at Muhammadiyah Riau University located on Jl. Tuanku Tambusai No.135, Delima, Kec.tampan, Pekanbaru City Riau. which has 7 floors without a basement. This research aims to analyze and determine the level of reliability of the Riau Muhammadiyah University Rectorate building, so that when the building is used, the risk of fire in this building can be minimized. This research uses a method, namely the Analytical Hierarchy Process (AHP) method where this method is carried out by comparing elements that are more important than other elements assisted by using Expert choice 11 software. The elements used are taken from Permen PU No. 26 of 2008, namely site completeness, rescue facilities, passive protection systems, and active protection systems. The results obtained from this method are weighted in the form of numbers, where the numbers obtained have the level of each building reliability,classified into less, sufficient or reliable reliability. for the Muhammadiyah Riau University Rectorate building. The reliability value of the Muh University Rectorate Building The reliability value of the Muhammadiyah Riau University Rectorate Building with the AHP method obtained a value of 81.6%, so that it is included in the category in